Spanish Adult Students’ Intention- Behaviour Toward MOOCs During the COVID-19 Pandemic - Escobar Alvarez, Maria Ángeles; Ciancio, Julie (Íkala, Revista de Lenguaje y Cultura, 2021)
Many Spanish students need to learn English beyond the age of 25 to be able to find a job or be further promoted. Unfortunately, those who attempt to pass a university entry-qualifications test often lack the required academic level. To help them achieve this goal, they are usually provided with learning materials and supportive digital resources. During the covid-19 pandemic, the need for online resources increased. This is why the National Distance Education University offered a massive open online course (mooc) on elementary English. The main goal of this contrastive qualitative study was twofold: First, it attempted to explore adult students’ intention-behaviour while taking the course. Secondly it delved into students’ satisfaction with this type of courses during two different years: 2017 and 2020 when the pandemic had a clear impact on distance education. For this purpose, the study used a comprehensive post-questionnaire given at the end of both courses. The data revealed a few significant differences regarding students’ satisfaction, intentions, perceptions, and interests in contexts where face-to-face-learning was not an option. These findings suggest that mooc should be considered as an alternative way to build specific content in situations of crisis.